(untitled) (Ágora de Heterodoxias, 2018)
This article aimed to explore the lifestyle of pregnant adolescents to build knowledge that guides the intervention of community nursing within the system of primary health care. From the methodological point of view, the article was framed within the qualitative paradigm, using the phenomenological approach of Amadeo Giorgi, and four adolescents between 16 and 19 participated. The semi-structured interview was the technique for collecting data. The reading and re-reading of the interviews was the previous step for the discrimination of the sense units using the hermeneutics in the interpretation of the data, and the computational program Atlas.ti in its organization. After the intervention of the community nurse, the most significant results in the majority of the adolescents showed an acknowledgment about the importance of assuming a healthy behavior. The pregnant adolescents did not express interventions of the nurse in regards of the importance of restful sleep, the use of free time or recreation, which led to the need of strengthen the preparation of the community nurse. Regarding factors detrimental to health, it was observed in one of the pregnant adolescents that alcohol consumption persisted during pregnancy, despite having received information on adverse effects. As a conclusion, the lack of awareness regarding the consumption of nutritious foods is an element that affected the optimal diet of pregnant adolescents.